ANALISIS PENETAPAN ANGKA KREDIT KENAIKAN JABATAN FUNGSIONAL GURU SMAN/SMKN DI DINAS PENDIDIKAN PROVINSI JAWA BARAT - Azmi Chairunissa Alfiantyi (Jurnal Tata Kelola Pendidikan, 2021)
The research entitled "Analysis of Determination of Credit Scores for Promotion of Functional Positions for SMAN / Vocational Teachers at the Education Office of West Java Province" in general this research is to find out and obtain an overview of the determination of credit scores and promotions / teacher positions in the Education Office of West Java Province. The method used in this research is descriptive using a qualitative approach, data collection techniques with interviews, observations, and documentation studies. The results showed that many teachers did not meet the requirements in following the determination of credit scores. The credit score is a unit of value for each item of activity and/or the accumulated value of the items of activity that must be achieved by a teacher in the context of fostering a career of rank and position. In accordance with the Joint Regulation of the Minister of National Education and the Head of the State Civil Service Agency Number 03/V/PB/2010 Number 14 of 2010 the official authorized to propose the determination of the credit score submits the proposal for determining the credit score to the official authorized to determine the credit score through the secretariat of the assessment team. For the flow in applying for the determination of the teacher credit score, the teacher first uploads the file on the OPAK (Online Determination of Credit Score) application, then the original file is sent to the KCD (Office Branch Office), then to the Provincial Education Office which is managed by the Development Section. In 2018 the December period that passed only 205 (20.9%) experienced an increase in 2019 the June period which passed 952 (69.1%) while in 2020 the June period decreased again to 488 (54.6%). At the 2020 credit score determination session, there was a decrease in teachers who submitted a trial from 2019 because there was no appeal period and the impact of the COVID-19 pandemic was one of the inhibiting factors.